DETERMINATION OF THE MINIMUM INHIBITORY CONCENTRATION OF THE ETHANOLIC EXTRACT OF KIPAHIT LEAVES ON THE GROWTH OF Propionibacterium acnes - Joko Priyanto Wibowo; Noor Aida; Islan Nor; Irfan Zamzani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Acne is a skin disorder characterized by inflammation in the form of comedones, papules, pustules, and nodules. The disease is caused by the gram-positive bacterium, Propionibacterium acnes. Treatment of the disease using antibiotic agents such as erythromycin and clindamycin has been reported to cause some side effects. Therefore, alternative antibacterial agents derived from natural products are required to reduce the occurrence of side effects. Kipahit (Tithonia diversifolia A. Gray) is one of the plants with pharmacological activities, such as antibacterial and antiprotozoal activities. The aim of this study was to determine the minimum inhibitory concentration (MIC) of a 96% ethanolic extract of kipahit leaves on the growth of P. acnes. Kipahit leaves were extracted through the ultrasound-assisted extraction (UAE) method. Minimum inhibitory concentration (MIC) was determined using the liquid dilution method. A serial dilution was performed to prepare a series of extract concentrations: 25%, 12.5%, 6.25%, 3.13%, 1.56%, 0.78%, and 0.39%. Whereas, clindamycin and DMSO 1% were used as positive and negative controls, respectively. Phytochemical screening showed that the 96% ethanolic extract of kipahit leaves contains flavonoids, alkaloids, saponins, steroids/triterpenoids, tannins, and phenolic compounds. In addition, the extract showed inhibitory activity against P. acnes at concentrations ranging from 25% to 1,56%. In contrast, the extract showed no inhibitory activity at concentrations of 0.78% and 0.39%. Further experiments confirmed that kipahit leaf extract acted as a bacteriostatic agent (inhibiting bacterial growth) at a minimum concentration of 1.56%. Keywords: Acne, Propionibacterium acnes, Kipahit, MIC